Experiências de inverno no Seridó Potiguar - Silva, Neusiene Medeiros da (2013)
The knowledge known as "winter experiences" has been developed for centuries among country people in the Brazilian Northeast hinterlands. It consists in the systematic observation of the nature to forecast and protect people against the effects of droughts. This knowledge is transmitted orally through generations. These experiences are guided by the observation of the behavior of fauna, flora, stars, the weather in the holy days and other very specific aspects of the lives of country people. Almost all country people living in the rural area know at least one experience, but the Prophets of Rain are known as the communicators of winter prophecies formulated from the observation of the experiences. The country person is identified as a Prophet of Rain because of his close relationship with nature and his ability to forecast. No matter if the prophecies are always right, he possesses a vital social role, as his practices contribute to prevent, ease and encourage other people. The main aim of this work is to analyze the role of the winter experiences for the country people in the Seridó Potiguar. In this sense, we sought to understand to what extent this knowledge still orients the productive practices of farmers living in this region and identify which factors instigate the observation of winter experiences nowadays. 241 questionnaires were applied to farmers in the rural cities of Acari, Caicó, Parelhas and Lagoa Nova and interviews were conducted with 15 Prophets in the Seridó. The methodological framework of this work is the analysis of content proposed by Bardin (2010). In this study area, the experiences exert influence and relevance to the country people in the Seridó, because they consider them as a way to ease their anguishes face the possible drought in the region. The major role of the Prophet is to feed the hope of country people for better days, rather than contribute for the organization of the productive activities. Among the interviewed people, the forecast from the observation of winter experiences have greater credibility than the meteorological and disseminated by media. The Prophets of Rain base their prophecies on the set of natural elements present in the environment. Many factors stimulate the winter experiences by the Prophets nowadays, as cultural transmission, age, relationship with nature, level of education, faith, among others, but specially the productive activities (agriculture and cattle raising) and the droughts. The winter means abundance and happiness in this region and the experience is one of the ways that people find to minimize the anxiety and, according to their possibilities, to prepare for a year of droughts or for winter